Defek Konotrunkal Jantung - Herlina Dimiati; Silfia Yasmine Lubis (The Indonesian Heart Association, 2015)
Conotruncal anomalies comprise a diverse group of congenital heart defects involving the outflow tracts of the heart and the great .They are a leading cause symptomatic cyanotic cardiac disease diagnosed in utero. Conotruncal anomalies can be diagnosed by prenatal echocardiography with a high degree of accuracy. The overall prognosis for fetuses with a conotruncal anomaly is poor